ChemInform Abstract: A 200‐Fold Quantum Yield Boost in the Photoluminescence of Silver‐Doped AgxAu25‐x Nanoclusters: The 13th Silver Atom Matters. Issue 22 (3rd June 2014) - Wang, Shuxin; Meng, Xiangming; Das, Anindita; Li, Tao; Song, Yongbo; Cao, Tiantian; Zhu, Xiuyi; Zhu, Manzhou; Jin, Rongchao
Abstract Two series of Ag‐doped AgxAu25‐x nanoclusters are prepared by two different routes.